Education of the Movement of Landless Rural Workers: a space of resistance to coloniality and its mechanisms of power - Yohana Marcela Sierra Casallas; Darci Secchi (Universidade Federal do Norte do Tocantins, 2020)
This paper is part of an investigation linked to the Post-graduate Education Program in the Federal University of Mato Grosso, research on Social Movements, Politics and Popular Education, Cuiabá, with the support of the Coordination for the Improvement of Higher Education Personnel (CAPES). Its purpose is to analyze the pedagogical and educational initiatives developed in rural schools, under the coordination of the Movement of Landless Workers (MST) in Mato Grosso, as a process of resistance to coloniality and its mechanisms of power. This is a qualitative research, developed with the teachers and directors of the Florestan Fernandes National School located in the October 12's Settlement. The research tools used were: semi structured interviews, participant observation and field journals. Based on the interviews, it can be seen that the MST's schools are constituted from an anti-hegemonic conception, with different pedagogical practices. The field journals analysis reveals that this school implements the philosophical and pedagogical principles of the Movement, although financed by the public sector.